LTF and DEFB1 polymorphisms are associated with susceptibility toward chronic periodontitis development. - Zupin, L; Robino, A; Navarra, C O; Pirastu, N; Di Lenarda, R; Gasparini, P; Crovella, S; Bevilacqua, L (Oral Dis, 2017)
OBJECTIVES: Chronic periodontitis is a common pathological condition that affects the supporting tissue of the teeth, leading to progressive alveolar bone destruction and teeth loss. The disease is caused by bacteria and derives from an altered host immune and inflammatory response, also involving different factors such as the oral hygiene, smoking, and genetic background. The innate immune response, the first line of host defense, could also play an important role in the susceptibility to chronic periodontitis. In this study, we evaluated the possible association between periodontal disease and seven genetic variations within DEFB1 and LTF genes, encoding for β-defensins 1 and lactoferrin (two members of oral innate immune system), in an Italian isolated population. SUBJECTS AND METHODS: DEFB1 5'UTR g. -52G>A (rs1799946), g. -44C>G (rs1800972), g. -20G>A (rs11362), 3'UTR c*5G>A (rs1047031), c*87A>G (rs1800971), LTF p.Ala29Thr (rs1126477), and p.Lys47Arg (rs1126478) single nucleotide polymorphisms (SNPs) were analyzed in 155 healthy individuals and 439 chronic periodontitis patients from North-East Italy. RESULTS: Significant associations were found between periodontitis and g. -20G>A (rs11362) and g. -44C>G (rs1800972) SNPs in DEFB1 gene as well as p.Ala29Thr (rs1126477) and p.Lys47Arg (rs1126478) SNPs in LTF gene. DISCUSSION: Our results suggest the involvement of DEFB1 and LTF genetic variations in the susceptibility toward development of periodontitis.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; beta-Defensins; Case-Control Studies; Chronic Periodontitis; Female; Genetic Predisposition to Disease; Humans; Lactoferrin; Male; Middle Aged; Polymorphism, Single Nucleotide; Young Adult